The Building of Bullock Harbour - Shotton, Elizabeth (Cahiers d'histoire, 2019)
There are hundreds of small harbours on the Irish coastline that were used for trade or fishing until the mid-twentieth century when these activities were centralized to major ports. Many date back hundreds of years, representing a system that linked local economies, which are critical to understanding Irish history. Yet, because many were built by estate owners or local communities, archival records rarely exist. Understanding the development of these modest structures demands a new methodological approach: through the innovative use of LiDAR scan data to interrogate what little visual and textual evidence exists to figuratively unearth the location of earlier structures.